The Realm of the Earth: Simultaneous Broadcasting and World Politics in Interwar Cinema - Cowan, Michael (Intermédialités / Intermediality)

(untitled) (Revue intermédialités (Presses de l’Université de Montréal), 2014)
This article discusses intermedial relations between film and new technologies of broadcast—telegraph, radio and television—in interwar Europe, culminating in a reading of Abel Gance’s largely forgotten radio film La fin du monde (1931). It argues that efforts to reposition film in relation to the new technologies of broadcast helped to catalyze both new forms of montage and new understandings of film as a medium that might forge political communities on a world scale.